1997
DOI: 10.1016/s0925-4773(96)00644-2
|View full text |Cite
|
Sign up to set email alerts
|

Two new regulatory elements controlling the Drosophila Sgs-3 gene are potential ecdysone receptor and fork head binding sites

Abstract: We identified two regulatory elements in the upstream region of the Drosophila Sgs-3 gene which are both able to bind the ecdysone receptor (EcR/USP) and the product of the fork head gene. Interestingly, only one of the EcR/USP binding sites is able to recognize in vitro-translated EcR/USP, which provides evidence for the existence of different receptor forms having different DNA binding specificities. Deletions of the elements lead to a reduced accumulation of Sgs-3 mRNA without altering the temporal expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…The gene encoding the SGS-3 protein has been described for several species of Diptera as having an ecdysone-responsive element. Levels of ecdysone control the level of transcription of Sgs-3 in Drosophila melanogaster in an inversely proportional manner (17). Because ecdysone has been described for ticks, it is expected that hormone response element genes are present in ticks (4), specifically in the reproductive tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene encoding the SGS-3 protein has been described for several species of Diptera as having an ecdysone-responsive element. Levels of ecdysone control the level of transcription of Sgs-3 in Drosophila melanogaster in an inversely proportional manner (17). Because ecdysone has been described for ticks, it is expected that hormone response element genes are present in ticks (4), specifically in the reproductive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The Oi312-SGS-3 molecule was decreased in the ovaries and nearly abolished in the midguts and salivary glands of the Rickettsia-infected ticks. Although this transcript is likely under hormonal regulation, as are its paralogs in Drosophila (17), the significance of Rickettsia-mediated modulation is not clear. It is an exciting possibility that an unknown rickettsial receptor is in fact regulated either by this molecule or by the hormone.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether Fkh regulation of SG1 and SG2 is direct, we first asked if Fkh binds in vitro to the sequences in each enhancer that match published core Fkh-binding sites (Lehmann and Korge, 1996;Mach et al, 1996;Lehmann et al, 1997). Fkh bound strongly to site 'd' in the SG1 972 enhancer, as determined by electrophoretic mobility shift assays (EMSA) (Fig.…”
Section: Fork Head Is Required For the Salivary Gland Expression Of Smentioning
confidence: 99%
“…When we began our analysis of Fkh regulation of SG1 and SG2, we looked for every potential direct binding site within the SG1 and SG2 enhancers using data from three different studies (Lehmann and Korge, 1996;Mach et al, 1996;Lehmann et al, 1997), which revealed a seven bp core consensus Fkh-binding site. Although we found four such consensus sites within each enhancer, not all of the sites were bound by Fkh protein in vitro.…”
Section: Research Articlementioning
confidence: 99%
“…In contrast to several of the Sgs genes, no ecdysoneresponse elements nor a forkhead-binding site were identified. The latter has been shown to be functional in the promoters of Sgs genes [31][32][33]. In close proximity to the TATAAA element, which also serves as a putative recognition site for binding of the B-factor, the Engrailed protein, TATA-box-binding protein (TBP), transcription factors TFIIB, TFIIα and TFIIFβ, and three putative GC boxes were identified ( Figure 5).…”
Section: Figure 3 Phylogram Of Gfat Amino Acid Sequences Created By Tmentioning
confidence: 99%